High altitude disease on the Tibetan plateau. - Wu, T.Y.; Li, Y.; Wang, Z.G.; Re., R. L.; Den, G. (Acta Andina, 2025)
In China, the Qinghai-Tibetan plateau is the highest and largest plateau in the world, in which lives both Tibetan natives and Chinese immigrants (Han). This paper deals with questions concerning high altitude disease (HAD) on the plateau. There are three main serious altitude health problems. First high altitude pulmonary edema (HAPE). A high incidence is observed between newcomers to high altitude and lower incidence of HAPE after reascent of Tibetans are quite different with reports from North America and from the Andes. Second, high altitude heart disease (HAHD). The infants and children are aspeciall y at risk. Most infants affected by this disease are from Han origin, and presented severe congestive cardiac failure due to pulmonory hypertension fewe months after birth or after arrival to high altitude. Autopsies show right ventricular hypertrophy and muscular thickening of peripheral pulmonary arteries. The average mortality was 15%, so that infantile HAHD is a fatal disease. Third, Monge’s disease or chronic mountain sickness (CMS). 15 patients with CMS in indigenous Tibetans were observed during 1991 -1993. Pathophysiological studies werw performed. Both epidemiological and clinical investigative data show that CMS exists on the Qinghai-Tibetan plateau.